Endoscopic submucosal dissection for superficial esophageal squamous cell neoplasms - Honda, Kuniomi (Baishideng Publishing Group Co., Limited, 2012)
Endoscopic resection is an effective treatment for non-invasive esophageal squamous cell neoplasms (ESCNs). Endoscopic mucosal resection (EMR) has been developed for small localized ESCNs as an alternative to surgical therapy because it shows similar effectiveness and is less invasive than esophagectomy. However, EMR is limited in resection size and therefore piecemeal resection is performed for large lesions, resulting in an imprecise histological evaluation and a high frequency of local recurrence. Endoscopic submucosal dissection (ESD) has been developed in Japan as one of the standard endoscopic resection techniques for ESCNs. ESD enables esophageal lesions, regardless of their size, to be removed en bloc and thus has a lower local recurrence rate than EMR. The development of new devices and the establishment of optimal strategies for esophageal ESD have resulted in fewer complications such as perforation than expected. However, esophageal stricture after ESD may occur when the resected area is larger than three-quarters of the esophageal lumen or particularly when it encompasses the entire circumference; such a stricture requires multiple sessions of endoscopic balloon dilatation. Recently, oral prednisolone has been reported to be useful in preventing post-ESD stricture. In addition, a combination of chemoradiotherapy (CRT) and ESD might be an alternative therapy for submucosal esophageal cancer that has a risk of lymph node metastasis because esophagectomy is extremely invasive; CRT has a higher local recurrence rate than esophagectomy but is less invasive. ESD is likely to play a central role in the treatment of superficial esophageal squamous cell neoplasms in the future.